Matching Risks with Instruments in Development Banks. Issue 2 (3rd April 2022) - Griffith-Jones, Stephany; Spiegel, Shari; Xu, Jiajun; Carreras, Marco; Naqvi, Natalya
ABSTRACT: This paper explores how development banks should deploy appropriate financial instruments to encourage real economic risk-taking while minimizing financial engineering risks. We distinguish real economic risks from financial engineering or intermediary risks and argue that using complex financial instruments to leverage additional private financing may undermine policy steer and lead to too much risk being taken by development banks. We then explore comparative advantages of different financial instruments such as loans, guarantees, equity, and insurance in tackling risks in normal times. Then we synthesize common features of development banks' responses to the COVID-19 crisis. Finally, we propose future research directions.